Support and Advice for the Participation of Non-working Mothers at PTM Posbindu in Medan City - Sri Yusnani; Ida Yustina; Nurmaini Chalik (RIRAI Publisher, 2023)
The disinfected illness or PTM is the chronic illness which is disinfected one to another. Globally, 70% of the death in the world caused by PTM. The SPM target states that every Indonesian citizen aged 15-59 years will receive health screening according to standards, while the percentage of PTM screening aged ≥ 15 years in the city of Medan in 2020 is 15%. The aim of the study was to analyze the relationship between tool's support and the participation of non-working mothers at Posbindu PTM in Medan City. This type of quantitative research with survey methods. Cross-sectional study design. The total population is 21,485 people, the total sample is 100 people. Data were analyzed by Rank Spearmen correlation. The results of the Rank Spearman test obtained a value of P=0.029 (P <0.05) meaning that there is a significant relationship between tool's support and the participation of non-working mothers in Posbindu PTM in Medan City. Participation of non-working mothers can be increased by socializing posbindu, increasing supporting facilities and infrastructure, increasing the ability to establish partnerships.